Understanding lithiation induced volume variations and its impact on porous cobaltite (LiCo2O4) for Li-ion battery cathodes - L. Maake; B. Shibiri; P.E. Ngoepe; R.S. Ledwaba (Next Materials)
Spinel LiCo2O4 exhibits superlative electrochemical performance due to its high Li+ diffusion rate; meanwhile, porous nanomaterials offer large surface areas and pore volume, allowing materials to expand freely with lithiation. However, it is very difficult to synthesise LiCo2O4 through conventional methods. As such, it has become redundant over the years. Therefore, herein, molecular dynamics simulation methods are employed to investigate the porosity and structural changes of three lithiated Li1+xCo2O4 (0 ≤ x ≤ 1) nanoporous materials with cell dimensions of 67, 69, and 75 Å during the discharge process to improve their cycling performance and structural stability. The radial distribution functions showed structures, which have sufficiently amorphised and recrystallised with lithiation. Furthermore, the simulated XRDs showed peaks that correspond to the formation of the cobaltite LiCo2O4 spinel when compared to experimental results. In addition, the XRDs also show significant peak shifts, splits, and broadening with increasing lithium concentration. This may be attributed to structural changes and phase transitions from cubic to tetragonal symmetry since multi-grained structures are observed at the Li1.75Co2O4 concentration. Pore size changes in the materials are also observed with increasing lithium concentration, and the nanoporous materials experience some volume changes during the discharge process. Nanoporous 69 Å material is observed to have a great overall volume increase compared to its counterparts. However, all the nanoporous materials retain their structural integrity upon full lithiation at Li2.00Co2O4; indicating their potential to enhance the cycling performance and structural stability of LiCo2O4 cathodes.